VD_FINDINFO Décision / 2014 / 62 vom 24. Januar 2014 - VD Tribunal cantonal (2014)
RISQUE DE FUITE, RISQUE DE COLLUSION, PROLONGATION, DÉTENTION PROVISOIRE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 393 al. 1 let. c CPP (CH)